2011
DOI: 10.1007/s12011-011-9091-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Trace Elemental Profiles in Blood Samples of Indian Patients with Leukoplakia and Oral Submucous Fibrosis

Abstract: In order to ascertain possible correlation between alterations in trace elemental profile and the progression or regression of two most common potentially malignant disorders affecting oral cavity, namely oral submucous fibrosis and leukoplakia, blood from 60 patients from each group of patients as well from 30 healthy individuals was analyzed for elemental profiling employing EDXRF technique. Out of the 16 detected elements (K, Si, Ca, V, Cr, Ni, Mn, Fe, Cu, Zn, Se, Br, Rb, Sr, Co, and Pb), Mn, Fe, Zn, Br, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…[15,30] Contrary to the results of the present study, Ray et al, indicated that serum value of zinc in patients with leukoplakia had clearly decreased. [31] This finding may be related to the different nature of lesions. Moreover, values of zinc in patients with cancer were close to the normal range, while the individuals of control group showed lower values, which probably reveals nutritional deficiencies in Iranian population as shown in several studies.…”
Section: Discussionmentioning
confidence: 98%
“…[15,30] Contrary to the results of the present study, Ray et al, indicated that serum value of zinc in patients with leukoplakia had clearly decreased. [31] This finding may be related to the different nature of lesions. Moreover, values of zinc in patients with cancer were close to the normal range, while the individuals of control group showed lower values, which probably reveals nutritional deficiencies in Iranian population as shown in several studies.…”
Section: Discussionmentioning
confidence: 98%
“…Evaluation of Zn and Cu has revealed correlation between various disease states as well as the healthy or cured condition (Ray et al 2011;Reza et al 2011). We have also seen that the status of these micronutrients have been changed towards normalcy along with the treatment with Amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
“…Thus increasing attentions have been put forward in analyzing the trace elements in the KA patients' blood in order to perform rapid, sensitive, economical and reliable diagnosis (Rastegar et al 1984). The present study has been undertaken to evaluate the status of trace element level in the blood of Indian KA patients with the help of particle induced X-ray emission (PIXE), a very sensitive, powerful yet non-destructive multi-elemental analytic technique (Yin et al 1987;Sudarshan et al 2000;Ray et al 2011;Kumar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Zn stabilizes insulin structure [23,24], maintains normal dark adaptation capacity [25,26], and is a component of salivary proteins that promote the sense of taste and appetite [27,28]. It is involved in iron transport and transfer [29,30,31] and enhances the immune system [32,33,34]. Zn can inhibit lipid peroxidation and thiol oxidation of biomembranes, and along with copper-protein, catalase, and vitamin E, maintains cell structure [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Zn can inhibit lipid peroxidation and thiol oxidation of biomembranes, and along with copper-protein, catalase, and vitamin E, maintains cell structure [35,36,37,38]. Zn deficiency causes digestive disorders, delayed sexual maturity/development of secondary sexual characteristics resulting in stunted growth, skin disease, stomatitis, alopecia [29,30,39], and can impair immune function. Zn overdoses can cause metal fume fever, reduce serum high-density lipoprotein-cholesterol levels, and lead to iron deficiency anemia and copper deficiency [40,41].…”
Section: Introductionmentioning
confidence: 99%